Correlation-Based Reception Method of Radio Light with Spatial Resolution and Its Implementation - Petrosyan, M. M.; Ryzhov, A. I. (Journal of communications technology & electronics, 2023)
A method for receiving ultra-wideband noise-like microwave radiation, “radio light,” based on the correlation reception of signals from spatially separated receiving antennas, is considered in order to further efficiently form images of a medium illuminated by radio light. A mathematical model has been developed to study the formed response of the receiving system and evaluate the influence of the signal accumulation time on its dynamic range. One-dimensional responses of the correlation receiving system to point sources of radiation, which were used as radio light sources, are obtained. An experimental model of a radio light correlation receiver has been developed and physical experiments have been carried out with it, confirming the results of the simulation, as well as the efficiency of the proposed approach in general.